Labisia pumila improves wound healing process in ovariectomized rat model - Ahmad, Shihab Uddin; Shuid, Ahmad Nazrun; Mohamed, Isa Naina (Bangladesh Journal of Pharmacology, 2018)
The purpose of this study was to determine the wound healing effect of Labisia pumila in the ovariectomized rat model. Ninety-nine Sprague Dawley female rats equally divided into nine groups; where five were control groups, and four were treated groups. The dressing was changed daily, starting from the wound induction until complete healing. The percentage of wound contraction was measured on day 0, 2, 5, 8, 9, 10, 11, 12 and 13. Three rats were sacrificed from each group on day 2, 5 and 8 respectively for evaluating of histological assessments. Wounds dressed with extract showed considerable healing and significantly healed faster compared to all control groups (p<0.05). Moreover, histological analysis revealed remarkable reduction in the scar width correlated with the enhanced collagen content and fibroblast cells, accompanied by a reduction of inflammatory cells in the granulation tissues. In conclusion, L. pumila may promote wound healing in postmenopausal rat model. Video Clip of Methodology: Ovariectomy and punch biopsy: 3 min 11 sec: Click to Watch